Cannabinoids in trigeminal neuralgia - Antonino Genovese (Publiediting, 2021)
Trigeminal neuralgia is the most common craniofacial pain syndrome. This disorder causes severe facial pain and is described as very acute, similar to an electric shock to the jaw, eye region, teeth or gums. The authors present a clinical case involving a 46-year-old patient with trigeminal neuralgia; in this study, cannabinoid treatment (19% THC; <1% CBD) showed good pain relief.